Management of land relations and their impact on production in agriculture of the Kyrgyz Republic - Semenov S.R.; Semenov N.S. (BIO Web of Conferences)
The modern development of land and production relations in agriculture are becoming a priority, since the agricultural sector can take a leading position in transforming the country’s economy. The study is aimed at clarifying the problems of theoretical and practically oriented foundations for the formation of land relations management and their impact on the production component of the industry. Theoretical positions and conclusions are formulated within the framework of the concept of sustainable development of the country's economy, which determines the further direction of the formation and management of land relations that actively influence agricultural production. This study showed the possibilities of managing the main resource of agricultural production and its role in the further distribution by categories of farms, thereby highlighting peasant (farm) farms as the main farms in the creation of gross agricultural output. Based on the study, it is recommended to improve the system of managing land relations, including strengthening the legislative framework, creating a unified agricultural information system for monitoring land, developing a program for the use and management of land areas that, for one reason or another, are not used in crop rotation and tend to decline.